2014
DOI: 10.2174/1874091x01408010044
|View full text |Cite
|
Sign up to set email alerts
|

Acute Phase Response: Implication in ST-segment Elevation Myocardial Infarction

Abstract: We aimed to investigate the relation between serum inflammatory markers, 25OHvit-D3 and oxidative stress markers, namely paraoxonase1-arylesterase (PON1-ARE), total antioxidant status (TAS) and total oxidant status (TOS) in 30 male patients with ST–elevation myocardial infarction(STEMI) . There was negative correlation between tumor necrosis factor alpha and ARE; positive correlations between serum amyloid A(SAA) and oxidative stress index, SAA and TOS, 25OHvit-D3 and ARE. There was no statistically significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…In concordance with this evidence, in the VOHF study, we have found that CEC was directly related to HDL size, with s‐HDL being inversely related to CEC . This paradoxical evidence on the presence of high levels of s‐HDL in CVD, together with s‐HDL being more functional than l‐HDL, may be explained by the hypothesis that increased s‐HDL particles in the serum may indicate an aberration in the maturation of s‐HDL particles, therefore increasing the risk of CVD . According to this evidence, an enhancement of HDL maturation was observed in the VOHF study, surely due to the increase in LCAT activity reported after FVOOT intake .…”
Section: Resultsmentioning
confidence: 93%
“…In concordance with this evidence, in the VOHF study, we have found that CEC was directly related to HDL size, with s‐HDL being inversely related to CEC . This paradoxical evidence on the presence of high levels of s‐HDL in CVD, together with s‐HDL being more functional than l‐HDL, may be explained by the hypothesis that increased s‐HDL particles in the serum may indicate an aberration in the maturation of s‐HDL particles, therefore increasing the risk of CVD . According to this evidence, an enhancement of HDL maturation was observed in the VOHF study, surely due to the increase in LCAT activity reported after FVOOT intake .…”
Section: Resultsmentioning
confidence: 93%
“…Pro-inflammatory cytokines (IL-1 beta and Il-18), products of lipid peroxidation (oxLDL), and growth factors are potent apoptotic stimuli for endothelial cells [ 50 - 56 ]. In fact, HDL protects vascular endothelial cells from TNF-α-induced apoptosis [ 57 , 58 ]. The apolipoprotein composition of HDL affects its anti-apoptotic activity, with apoA-I-containing particles being the most effective [ 20 - 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…[47] This paradoxical evidence on the presence of high levels of s-HDL in CVD, together with s-HDL being more functional than l-HDL, may be explained by the hypothesis that increased s-HDL particles in the serum may indicate an aberration in the maturation of s-HDL particles, therefore increasing the risk of CVD. [60,61] According to this evidence, an enhancement of HDL maturation was observed in the VOHF study, surely due to the increase in LCAT activity reported after FVOOT intake. [42] Similarly, the EUROLIVE and the PREDIMED studies demonstrated that the intake of phenol-rich VOOs induced the formation of larger HDL particles, and increased CEC, LCAT, and CETP activities.…”
Section: Hdl Lipid Compositionmentioning
confidence: 72%